Toward Stimuli‐Responsive Dynamic Thermosets through Continuous Development and Improvements in Covalent Adaptable Networks (CANs). Issue 20 (14th February 2020) - Podgórski, Maciej; Fairbanks, Benjamin D.; Kirkpatrick, Bruce E.; McBride, Matthew; Martinez, Alina; Dobson, Adam; Bongiardina, Nicholas J.; Bowman, Christopher N.
Abstract: Covalent adaptable networks (CANs), unlike typical thermosets or other covalently crosslinked networks, possess a unique, often dormant ability to activate one or more forms of stimuli‐responsive, dynamic covalent chemistries as a means to transition their behavior from that of a viscoelastic solid to a material with fluid‐like plastic flow. Upon application of a stimulus, such as light or other irradiation, temperature, or even a distinct chemical signal, the CAN responds by transforming to a state of temporal plasticity through activation of either reversible addition or reversible bond exchange, either of which allows the material to essentially re‐equilibrate to an altered set of conditions that are distinct from those in which the original covalently crosslinked network is formed, often simultaneously enabling a new and distinct shape, function, and characteristics. As such, CANs span the divide between thermosets and thermoplastics, thus offering unprecedented possibilities for innovation in polymer and materials science. Without attempting to comprehensively review the literature, recent developments in CANs are discussed here with an emphasis on the most effective dynamic chemistries that render these materials to be stimuli responsive, enabling features that make CANs more broadly applicable. Abstract : Recent developments in covalent adaptable networks (CANs) are discussed with an emphasis on the most effective dynamic covalent chemistries (DCCs) that render these materials stimuli‐responsive, enabling features that make CANs broadly applicable across diverse materials science disciplines. Recycling, self‐healing, and 3D printing are discussed, amongst others.